Psychological and pedagogical support for overcoming speech anxiety in students in the process of learning a foreign language - Ovsiannikova, Hanna; KRAINENKO, Olena; Petrova , Olha (Educological discourse, 2026)
The article examines speech anxiety in foreign language learning and substantiates psychological and pedagogical support as a holistic, multi-level system of assistance. The relevance of the topic is determined by the fact that elevated anxiety during oral performance reduces learning activity, impairs communication quality, intensifies avoidance of speaking, and reinforces negative expectations about one’s own performance. The purpose of the article is to generalize current theoretical approaches to speech anxiety, identify the factors of its formation in the student environment, and justify a conceptual model of psychological and pedagogical support for its reduction. The methodological basis is a theoretical-conceptual analysis, comparison, synthesis, and systematization of contemporary research on foreign language anxiety and supportive educational environments. The novelty of the study lies not in addressing speech anxiety as such, but in proposing an integrative model that combines psychological and pedagogical mechanisms within a single support framework and in explicating the criteria by which its components were selected: empirical recurrence in the literature, modifiability in educational practice, and correspondence to the logic of multi-level support. The article outlines the key support mechanisms: diagnostics and monitoring of anxiety level, psychoeducation regarding the nature of errors and evaluation, development of self-regulation skills, gradual increase in the complexity of oral speech (gradual exposure), organization of safe group interaction, and the use of formative feedback without stigmatization. The expected result of implementing such support is a reduction in speaking avoidance, greater participation in communicative tasks, increased confidence, and stabilization of learning motivation. It is concluded that effective reduction of speech anxiety requires coordinated action by the teacher and the psychological service, together with orientation toward psychological safety, graduality, and a supportive culture of assessment.